Relevance of comorbidities and antithrombotic medication as risk factors for reoperation in patients with chronic subdural hematoma - Younsi, Alexander; Riemann, Lennart; Habel, Cleo; Fischer, Jessica; Beynon, Christopher; Unterberg, Andreas; Zweckberger, Klaus (Neurosurgical review, 2022)
In an aging Western society, the incidence of chronic subdural hematomas (cSDH) is continuously increasing. In this study, we reviewed our clinical management of cSDH patients and identified predictive factors for the need of reoperation due to residual or recurrent hematomas with a focus on the use of antithrombotic drugs. In total, 623 patients who were treated for cSDH with surgical evacuation between 2006 and 2016 at our department were retrospectively analyzed. Clinical and radiological characteristics and laboratory parameters were investigated as possible predictors of reoperation with univariate and multivariate analyses. Additionally, clinical outcome measures were compared between patients on anticoagulants, on antiplatelets, and without antithrombotic medication. In univariate analyses, patients on anticoagulants and antiplatelets presented significantly more often with comorbidities, were significantly older, and their risk for perioperative complications was significantly increased. Nevertheless, their clinical outcome was comparable to that of patients without antithrombotics. In multivariate analysis, only the presence of comorbidities, but not antithrombotics, was an independent predictor for the need for reoperations. Patients on antithrombotics do not seem to necessarily have a significantly increased risk for residual hematomas or rebleeding requiring reoperation after cSDH evacuation. More precisely, the presence of predisposing comorbidities might be a key independent risk factor for reoperation. Importantly, the clinical outcomes after surgical evacuation of cSDH are comparable between patients on anticoagulants, antiplatelets, and without antithrombotics.